2019
DOI: 10.21512/humaniora.v10i1.5248
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Students’ Preferences on the Oral Corrective Feedback in English as Foreign Language (EFL) Speaking Classroom

Abstract: This research aimed at investigating the male and female students’ preferences on the six types of Oral Corrective Feedback (OCF). This qualitative research used observation and interview to collect data. The observation was done to know the practice of the six types of OCF in speaking class and the interview was conducted to reveal the students’ preferences for OCF. The result from the observation shows that the lecturer mostly uses Explicit Correction to correct the students’ error. Then, the result from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
(24 reference statements)
0
5
2
Order By: Relevance
“…The findings are consistent with those of studies by Babushko and Solovei (2020) and Nguyen and Nguyen (2022), who found that students favored using delayed OCF near the conclusion of an utterance or after finishing an oral task. Students in this study favored receiving OCF right after making errors, which contradicts the findings of previous research (Amalia et al, 2019;Syakira & Nur, 2022;Patra et al, 2022;Sá nchez Centeno & Ponce, 2019;etc.). This finding is consistent with other studies that found EFL teachers preferred to offer delayed OCF, i.e.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The findings are consistent with those of studies by Babushko and Solovei (2020) and Nguyen and Nguyen (2022), who found that students favored using delayed OCF near the conclusion of an utterance or after finishing an oral task. Students in this study favored receiving OCF right after making errors, which contradicts the findings of previous research (Amalia et al, 2019;Syakira & Nur, 2022;Patra et al, 2022;Sá nchez Centeno & Ponce, 2019;etc.). This finding is consistent with other studies that found EFL teachers preferred to offer delayed OCF, i.e.…”
Section: Discussioncontrasting
confidence: 98%
“…However, (Margi and Vodopija-Krstanovi, 2018) found that students desire to acquire feedback as soon as they make errors, despite teachers' reluctance to offer early OCF. Additional research conducted in a university setting (Amalia et al, 2019;Patra et al, 2022;Sá nchez Centeno & Ponce, 2019) shows that students who prefer immediate to delayed feedback report that the former is more beneficial while the latter helps them forget their faults. However, according to (Babushko & Solovei, 2020) after EFL students have finished their speaking assignment or utterance, they prefer the delayed OCF, which does not seem to interrupt them as much or make them feel as bad about themselves (Nguyen and Nguyen, 2022).…”
Section: Corrective Feedback In the Literature: How Students And Inst...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the early 70's up to the present days, one of the crucial issues in teaching process, more specifically in error correction is how the teacher can correct the learner without de-motivating his learners. According to Tomczyk (2013) as cited by Amalia, Fauziati, and Marmanto (2019), plenty of discussions on errors and corrections in language classroom were still ambiguous because of the fact that the attitudes towards errors of both teachers and students differ, as well as error correction diverge depending on the approaches that are applied.…”
Section: Introductionmentioning
confidence: 99%